PENGARUH FIRM SIZE, WORKING CAPITAL, COMPANY EFFICIENCY,LIQUIDITY DAN LEVERAGE TERHADAP PROFITABILITAS PERUSAHAAN (Pada perusahaan Property, Real Estate dan Building Construction yang terdaftar pada Bursa Efek Indonesia Periode 2013-2018) - 1 Kadek Oka Swartana (Politeknik Negeri Lhokseumawe, 2021)
The purpose of this study is to examine the effect of firm size, working capital, company efficiency, liquidity and leverage on profitability as measured by the proxies of ROA and ROE. This research is a quantitative research. The type of data used is secondary data, namely financial data of property, real estate and building construction companies listed on the Indonesia Stock Exchange (IDX) during the period 2013-2018. The data source in this study was obtained from the official website of the IDX. The analysis technique used is multiple linear regression. The number of observations used in this study was 339 observations which were a combination of real estate, property and construction companies. The results show that firm size (SIZE), asset turnover, current ratio (CR) have a significant positive effect on the performance of Property, Real Estate and Building Construction companies listed on the Indonesia Stock Exchange, proxied by return on equity (ROA and ROE). Meanwhile, working capital turnover (WCT) and Leverage (LEV) have a significant negative effect on the performance of Property, Real Estate and Building Construction companies listed on the Indonesia Stock Exchange, which is proxied by return on equity (ROA and ROE).Keywords: firm size, working capital, company efficiency, liquidity, leverage, profitabilitas, property, real estate dan building construction